Kapasitas Dinas Pemberdayaan Perempuan Dan Perlindungan Anak Dalam Mengatasi Kenakalan Remaja Di Kota Sukabumi - Gihan Pangestu; Ike Rachmawati; Yana Fajar FY. Basori (Jayapangus Press, 2026)
The increasing incidence of juvenile delinquency and violence against children in Sukabumi City has become a growing concern, particularly in cases of physical, psychological, and sexual abuse. Data from the Technical Implementation Unit for Women’s Empowerment and Child Protection (UPT PPA) for 2022–2023 indicate a significant rise in reported cases and victims, challenging the institutional capacity of local government. This study aims to analyze the organizational capacity of the Women’s Empowerment and Child Protection Agency (DP3A) of Sukabumi City in responding to this escalation. A qualitative descriptive approach was employed through observations, in-depth interviews with agency leaders, UPT PPA officers, experts, and social workers, supported by document analysis. The analysis is guided by Grindle’s organizational capacity framework, which includes human resource development, organizational strengthening, and institutional reform. The findings reveal that DP3A demonstrates relatively adequate capacity in leadership, inter-sectoral coordination, and institutional commitment. However, these strengths are constrained by limited budget allocation, imbalance between workload and personnel, and reliance on externally driven training policies. This study contributes empirically by mapping local government institutional capacity in child protection governance within a public organizational context.